2012
DOI: 10.1111/1346-8138.12043
|View full text |Cite
|
Sign up to set email alerts
|

Local oxidative stress in interdigital tinea pedis

Abstract: Several skin diseases are believed to be associated with oxidative stress. Tinea pedis is an infection of the feet caused by fungi. The infectious diseases caused by dermatophytes are mainly related to the enzymes produced by these fungi. The cutaneous oxidative stress status of tinea pedis has not been demonstrated in the published work up to now. The aim of the present study was to evaluate the role of oxidative stress in affected skin areas in a group of patients with interdigital tinea pedis. Thirty-one co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…However, there is one study in humans. Ozturk et al reported that lipid peroxidation levels in scraping sample of TP patients increased more than control group as similar to our study [ 20 ]. This may be an indication of oxidative stress derived from inflammation in this lesional area.…”
Section: Discussionsupporting
confidence: 92%
“…However, there is one study in humans. Ozturk et al reported that lipid peroxidation levels in scraping sample of TP patients increased more than control group as similar to our study [ 20 ]. This may be an indication of oxidative stress derived from inflammation in this lesional area.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, Malassezia spp may lead to skin diseases such as seborrhoeic dermatitis, atophic dermatitis and psoriasis in addition to PV. Thus, in our previous study which investigated local oxidative stress in tinea pedis and seborrhoeic dermatitis, we found increased SOD and MDA levels in patients . Also, Emre et al .…”
Section: Discussionmentioning
confidence: 56%
“…Ozturk et al reported that antioxidant defense of lesional skin was higher compared to non-lesional skin in patients with interdigital types of tinea pedis. 21 Miraloglu et al also reported that there was a possible link between oxidative stress and imbalance of trace element status in lesional areas of tinea pedis patients. 22 When these studies are considered, it is thought that there might be a relationship between tinea pedis and oxidative stress ; however, there is not yet enough data to prove this interrelation.…”
Section: Accepted Manuscriptmentioning
confidence: 96%